Impact of Chronic Urticaria on Quality of Life in a Tertiary Level Hospital in Nepal - Anil Kumar Das; Upama Paudel; Navjot Brar; Ashish Karn (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Most healthcare providers recognize that urticaria is frequently difficult to treat but many do not realize the substantial negative impact, chronic urticarial (CU) has on patient’s quality of life (QoL). The questionnaire specifically developed to measure health related quality of life in chronic urticaria is the Chronic Urticaria Quality of Life (CU-Q2oL) questionnaire. This questionnaire has helped to define the effects and impact on patients.